Toward Global Welfare State Convergence?: Family Policy and Health Care in Sweden, Canada and the United States Special Issue on Globalization: Social Justice & Social Welfare - Olsen, Gregg M. (Journal of Sociology & Social Welfare, 2007)
Disclaimer: This summary was generated by AI based on the content of the source document.